Imminent Risk of Extirpation for Two Bottlenose Dolphin Communities in the Gulf of Guayaquil, Ecuador - Félix, Fernando; Burneo, Santiago F. (Frontiers in Marine Science, 2020)
A long-term study of a common bottlenose dolphin (Tursiops truncatus) population inhabiting the Gulf of Guayaquil, Ecuador (2º33' S, 79º20'W), has been carried out for almost 30 years. Similarly, as in other parts of the world, this population is structured socially and spatially in well-defined subunits or communities. Two of these communities, referred to as Posorja and El Morro, have been studied with major intensity in the last 10 years in the western inner estuary, among others to calculate population parameters that allow assessing their viability in time. Calculated parameters include annual abundance, age and sex composition, annual crude birth rate, calf survival, calf production interval, and average annual mortality/emigration. With these parameters and others derived from other better-studied populations, the trend of both subunits was modeled using the software Vortex. Results show that even under an optimistic scenery both communities will be extinct in the short (Posorja) and mid-term (El Morro), if current stressors continue. Most population parameters calculated in both communities show similar values as in populations elsewhere, but a very low calf survival in Posorja and high mortality/emigration ratios in adults, and probably in juveniles in both communities, contribute to revert this trend. Population deterioration seems to be the result of different human-induced threats such as fisheries, maritime traffic and others still not well assessed, as well as stochastic demographic events. We recommend taking actions in the short term to halt population decline addressing the major causes of mortality affecting these dolphin communities.